The soil structural stability determined by the QuantiSlakeTest: Linkage with soil porosity, water-stable aggregate fractions and soil chemical properties - Toon van Dael; Quinten Verwerft; Erik Smolders (Geoderma)
Recently, the QuantiSlakeTest (QST) was developed which records mass loss or gain of intact soil samples during submergence, but it is yet unclear how slaking relates quantitatively to soil structure. This study was set up to determine if the QST can be a quick and cost-effective alternative to established structure tests and can be linked to soil porosity, determined by the soil water retention curve, or to the water-stable aggregate (WSA, >250 µm) fraction obtained by wet sieving. This was performed in a comparative study with 22 soils collected in arable and pasture land with contrasting properties. The mass loss due to aggregate breakdown in the QST was smaller as soil organic carbon (SOC) content increased (r = 0.59), while SOC correlated weaker with the WSA fraction (r = 0.45) or with relative meso + macroporosity (> 30 µm; r = 0.53). The WSA correlated strongly to oxalate extractable Fe (Feox) in the soil (r = 0.63), conforming to earlier studies, but no such trend was found for Quantislake parameters, indicating that the QST captures a different aspect of soil structure than the wet sieving. The mass loss in the Quantislake decreased with increasing relative meso + macroporosity (r = 0.68), suggesting that soil resistance to aggregate breakdown is higher in soils with a large fraction of large pores than in soils with smaller average pore sizes. In a subset of 10 soils, root mass within each Kopecky ring was recorded. It showed that the QST and relative microporosity strongly correlated with the root mass in the sample (r = 0.77 and 0.71, respectively), showing the importance of roots on soil structure. The Quantislake parameters have a much larger variability among sampling replicates (CV = 75–––100 %) than the parameters of the two other methods. However, the Quantislake parameters differed much more among soils, leading to similar statistical power as wet sieving and the water retention curves. It is concluded that the QST is a useful additional index of soil structure in undisturbed soils. It even outperforms the wet sieving method to indicate mesoporosity and is thus better suited for studying, e.g., preferential flow.